The Chicken Trail: Following Workers, Migrants, and Corporations across the Americas - Kathleen C. Schwartzman (Cornell University Press, ILR Press, 2013)
The relationship between immigration and unemployment has become a particularly controversial topic in the United States. This book is about immigration and unemployment, but it is also about bi-national business restructuring and bi-national labor reorganization. The Chicken Trail ties them together. I have two goals in writing this book: fi rst, to outline and analyze the causes and consequences of immigration; and second, to dispel some of the common beliefs about immigration by replacing them with a more historically nuanced sociological analysis. While I do not directly engage the current debate, I offer an alternative framework for understanding the perplexing realities of immigration. This I take to be the sociological mandate: to offer an analysis of how society works and to refl ect on policy options. My hope is that those concerned with policy as well as students will fi nd it useful. I use metaphor of the chicken trail to investigate highly important patterns and transitions that affect America and the entire world. My framework folds the immigration story into the ongoing processes of U.S. and Mexico labor reorganization and displacement, which it then connects to global transformations. The labor displacement and immigration stories become part of a twenty-fi rst-century â€œGlobal Dilemmaâ€ and â€œAmerican Dilemma.â€ The Global Dilemma is that in developing nations, as rural survival continues to be undermined by international trade, people attempt to alleviate their poverty by abandoning fi rst the countryside and then their country. The American Dilemma is that economic transformations have left the United States with jobs that â€œnobody wants,â€ jobs that are shipped overseas, and jobs for which American workers are unqualifi ed. This book materialized out of several experiential and intellectual encounters. During visits to Alabama, U.S.A., and Sonora, Mexico, I was struck by the presence of unemployed young black men on the streets of Alabama and of ghost villages in Sonora. While America appears to have accepted growing populations of unemployed and imprisoned African Americans, it seems to be at war with, or at least ambivalent about, immigrants. The ambivalence I experienced in Arizona, currently a major thoroughfare for immigrant traffi c and engulfed in a fi restorm of contentious debate.